Qualidade da água subterrânea na região do distrito industrial de São Luís-MA - Oliveira, Jonas Maurício Bertoldo (2016)
The provisioning of water to the rural communities of São Benedito, Porto Grande, Inhaúma and Estiva, located next to the Industrial District of São Luís, Maranhão, Brazil, is made by using the local groundwater from tubular wells drilled by Companhia de Saneamento Ambiental (CAEMA) and private wells drilled by residents. In order to characterize hydrochemically the groundwater resources were determined fisical, chemical and bacteriological parameters of water samples from eight wells located in those communities, including four wells drilled by Universidade Federal do Maranhão (UFMA) and four tubular wells managed by CAEMA. The collection, preservation, storage and transport followed the Standard Methods for the Examination of Water and Wastewater (2005), the sampling method used was the low flow purging recommended by ABNT NBR 15.847:2010. The results of fisical, chemical analysis, notice changes in turbidity, hydrogen potential and dissolved oxygen parameters. The concentration of nitrite, nitrate and ammonia were maintained much lower than the maximal allowable limits from MS Ordinance nº 2.914/2011. As the concentrations of Ca+2 and Mg+2, doesn t have some maximal allowable limit for these ions in drinking water, the relation between these two ions is a good indicator of saline intrusion. The ionic ratio (rMg+2/rCa+2) shows medium value of 0,737 meq/L, indicative of freshwater, minimum value of 0,098 meq/L in the beginning of rainy season in tube well PT-04 and maximum value 4,135 meq/L in the beginning of dry season in tube well PT-01. Under the point of view of bacteriological quality, of total analyzed samples, 24 (75%) showed unsatisfactory microbiological quality to Total Coliforms and 4 (12,5%) to E. coli. The lack of infrastructure, with effluents disposition in septic tanks should be the responsible for the microbiological contamination found in this study, with serious implications for health s users of water resources.